A Narrative Review on Management of Cyanosis in Neonates: Management of Cyanosis in Neonates - Fayyaz, Maria; Shahbaz, Sumbal (Pakistan Journal of Health Sciences, 2023)
A bluish coloring of the skin or mucous membrane that is characteristic of the medical condition cyanosis can be visible around the lips, fingers, and toes. It is one of the indications of respiratory distress in infants that can be brought on by inadequate circulation and low levels of oxygenated blood. There are two basic causes of cyanosis, cardiac and pulmonary. Medical professionals are constantly very concerned about accurately diagnosing and treating newborns with congenital heart disease (CHD), despite the fact that prenatal diagnostic methods have significantly improved. Although they are physiologically entirely different from one another, ductus dependent congenital cardiac abnormalities can be divided into the ductus dependent systemic or pulmonary sickness. When developing the treatment plan, the clinical state and cardiac abnormalities must be taken into consideration. Many life-threatening conditions may not show signs right away after delivery, and the majority of clinical and physical symptoms are ambiguous, which makes a diagnosis difficult. Careful evaluation is required, and when clinical data, electrocardiograms, and chest X-rays are used. The newborn must be identified as being at such high risk right once, and prompt medical attention is essential to reducing mortality and morbidity